Cultural and leadership predictors of corporate social responsibility values of top management: a GLOBE study of 15 countries - Waldman, David A; Sully de Luque, Mary; Washburn, Nathan; House, Robert J; Adetoun, Bolanle; Barrasa, Angel; Bobina, Mariya; Bodur, Muzaffer; Chen, Yi-Jung; Debbarma, Sukhendu; Dorfman, Peter; Dzuvichu, Rosemary R; et al. (Journal of International Business Studies, 2006)
This paper examines cultural and leadership variables associated with corporate social responsibility values that managers apply to their decision-making. In this longitudinal study, we analyze data from 561 firms located in 15 countries on five continents to illustrate how the cultural dimensions of institutional collectivism and power distance predict social responsibility values on the part of top management team members. CEO visionary leadership and integrity were also uniquely predictive of such values.